Glucagonoma syndrome with serous oligocystic adenoma: A rare case report. Issue 43 (October 2017) - Gao, Yun; Wang, Chun; Gao, Yunyi; Chen, Huijiao; Peng, Bing; Chen, Weixia; Ran, Xingwu
Abstract: Rationale: Glucagonoma and pancreatic serous oligocystic adenoma (SOA) are rare neuroendocrine and exocrine tumors of the pancreas, respectively. The coexistence of glucagonoma syndrome (GS) and SOA is a rare clinical condition and has not yet been reported. Additionally, necrolytic migratory erythema (NME), a hallmark clinical sign of GS, is often misdiagnosed as other skin lesions by clinicians due to their lack of related knowledge, which delays diagnosis of GS and thus exacerbates the prognosis. Patient concerns: A 50-year-old male patient was admitted to our department because he presented with diabetes mellitus and a recurrent ulcerated skin rash. Prior to the accurate diagnosis, the skin manifestation was considered to be diabetic dermopathy. Diagnoses: The patient's fasting serum glucagon level was up to 871.5 pg/mL. A biopsy of the pancreatic tumor revealed a pancreatic neuroendocrine tumor, and immunoperoxidase staining revealed glucagon-positive cells. In addition, the histological examination of the pancreatic cystic lesions showed typical features of SOA. Interventions: The patient received a pancreaticoduodenal resection and radiofrequency ablation for the hepatic nodular lesion. Outcomes: One week after surgery, the glucagon concentration decreased to near normal levels. The cutaneous lesions spontaneously resolved within 4 weeks after surgery. Lessons: Because almost all glucagonomas are malignant or have malignant potential, their early recognition and correct diagnosis are very important for a better prognosis, especially in cases with NME as the only manifestation during the development of glucagonomas. It is therefore imperative that clinicians recognize NME early to make an accurate diagnosis.